Cover Image. (21st August 2019) - Zhang, Tongyu; Gao, Hongding; Sahana, Goutam; Zan, Yanjun; Fan, Hongying; Liu, Jiaxin; Shi, Liangyu; Wang, Hongwei; Du, Lixin; Wang, Lixian; Zhao, Fuping
Abstract : The cover image is based on the Original Article Genome‐wide association studies revealed candidate genes for tail fat deposition and body size in the Hulun Buir sheep by Tongyu Zhang et al., https://doi.org/10.1111/jbg.12402 . Cover image © Institute of Animal Science of Chinese Academy of Agricultural Science Images.